Urbanisation in North East Bihar: Pattern and Potential - Singh, Arun K. (National Geographical Journal of India, 2022)
North East Bihar surrounded on three sides by the rivers and on one side by the Himalayas has less than 10 per cent of the total population living in urban areas. Frequent floods, predominance of agricultural activities, lack of mineral resource base and unwillingness of the stakeholders are major factors for low level of urbanisation and it can be resolved through state intervention and suitable regional development strategy. This paper aims to examine the spatial spread of existing towns as well as the potential level of urbanization by taking into account urban and rural settlements. The paper is based on secondary data collected from census volumes and govt. documents